2014
DOI: 10.1039/c4ra08582e
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of self-assembling peptide nanofiber hydrogels for myocardial repair

Abstract: Myocardial infarction (MI) has become widely spread in clinical medicine, and results in massive loss of myocardium, ventricular remodeling and ultimately heart failure. Many strategies for repairing injured myocardium are under extensive investigation with some early encouraging effects, but cannot effectively prevent disease progression and heart failure. Cardiac tissue engineering has emerged as an increasingly important approach to repair infarcted myocardium. Self-assembling peptide nanofiber hydrogels ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 142 publications
(337 reference statements)
1
11
0
Order By: Relevance
“…This study confirmed that the introduction of conductive materials in nanofibrous scaffold increase their potential to mimic natural ECM especially in terms of their electrical conduction [42]. Further step ahead, small molecules like peptides [133] and functionalized gold nanoparticles were integrated in nanofibrous scaffold of polymethylglutarimide (PMGI), these gold nanoparticles were functionalized with adhesive peptides to enhance the cell attachment. Additionally, these scaffolds were also found to promote the differentiation of hiPSCs towards cardiomyocytes [134].…”
Section: Nanofiberssupporting
confidence: 63%
“…This study confirmed that the introduction of conductive materials in nanofibrous scaffold increase their potential to mimic natural ECM especially in terms of their electrical conduction [42]. Further step ahead, small molecules like peptides [133] and functionalized gold nanoparticles were integrated in nanofibrous scaffold of polymethylglutarimide (PMGI), these gold nanoparticles were functionalized with adhesive peptides to enhance the cell attachment. Additionally, these scaffolds were also found to promote the differentiation of hiPSCs towards cardiomyocytes [134].…”
Section: Nanofiberssupporting
confidence: 63%
“…Many previous studies have demonstrated that ionic self-complementary peptide-formed nanofiber scaffolds hold some promise in repairing damaged tissues or organs, including bone, 3 , 11 cartilage, 12 , 13 nerve, 14 , 15 heart, 16 , 17 as well as in wound healing. 18 , 19 The principle of molecular self-assembly guides the ionic self-complementary peptides to self-assemble into three-dimensional (3D) entangled nanofiber hydrogel scaffolds, which are analogous to those found in natural extracellular matrix (ECM).…”
Section: Introductionmentioning
confidence: 99%
“…RADA is a class of SAPs that can form supramolecular hydrogels upon mixing with the positively charged multivalent ions. The RADA-based hydrogels are biocompatible and biodegradable, mimic the nanofibrous structure of ECM, induce cell recruitment, and allow for sequence modification to render other bioactive functions [50,51]. These hydrogels have been used for the engineering of various tissues with low immunogenicity [52][53][54].…”
Section: Discussionmentioning
confidence: 99%